2010
DOI: 10.1038/ismej.2010.181
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the relative influence of bacterioplankton phylogeny and metabolism on lysogeny in reservoirs and lagoons

Abstract: Previous studies indicate that lysogeny is preponderant when environmental conditions are challenging for the bacterial communities and when their metabolism is reduced. Furthermore, it appears that lysogeny is more frequent within certain bacterial phylogenetic groups. In this comparative study from 10 freshwater reservoirs and 10 coastal lagoons, we aim to disentangle the influence of these different factors. In eight reservoirs and four lagoons, lysogeny was detected by induction assays with mitomycin C, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…We hypothesize that the viruses tend towards lysogeny in the anoxic core regardless of season consistent with considering the ETSP OMZ as an extreme environment. Consistent with this hypothesis, the number of inducible prophage was found to decrease with increasing bacterial metabolism in lagoons and reservoirs (Maurice et al ., ). Last, the microbes of the anoxic core may have been particle associated and not been sampled because of the pre‐filtering steps.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We hypothesize that the viruses tend towards lysogeny in the anoxic core regardless of season consistent with considering the ETSP OMZ as an extreme environment. Consistent with this hypothesis, the number of inducible prophage was found to decrease with increasing bacterial metabolism in lagoons and reservoirs (Maurice et al ., ). Last, the microbes of the anoxic core may have been particle associated and not been sampled because of the pre‐filtering steps.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, low microbial abundances have been correlated with a greater frequency of lysogeny in deeper low oxygen marine waters (Ram et al ., ; Corinaldesi et al ., ; Magagnini et al ., ). A higher abundance of lysogeny‐associated domains were identified in marine‐vent viromes compared with surface water viromes, leading to the hypothesis of higher levels of lysogeny in extreme environments (Maurice et al ., ; Anderson et al ., ). A similar switch in viral lifestyle may occur the anoxic core of the ETSP OMZ.…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, strong grazing control might likely maintain bacterial communities in a rapid growth condition (e.g., as in the exponential growth phase), resulting in high-energy metabolic expenditure (such as in the ATP paradox, see discussion above). Concerning viral infection, there is almost no information available on how viral infection varies with latitude or temperature, but it has been suggested that higher bacterial metabolic rates are usually associated with low viral induced lysogeny (Maurice et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…This high taxonomic diversity within the Proteobacteria coincides with a high degree of morphological diversity. Although the bacterioplankton community of the surrounding water was not investigated in the present study, Proteobacteria, Bacteroidetes and Actinobacteria are frequently reported from coastal waters (Fuhrman & Ouverney 1998, Longnecker et al 2005, Bouvier & Del Giorgio 2007, Maurice et al 2011. Surprisingly, neither Bacteroidetes nor Actinobacteria could be detected on the spherom cuticle.…”
Section: Composition Of the Biofilmmentioning
confidence: 47%